Correlation analysis and path coefficients for yield components in nine experimental tomato lines - Gonzalo Quispe-Choque; Nancy Huanca-Alanoca (Journal of the Selva Andina Research Society)
The objective of the research was to analyze the main variables related to tomato yield, and to guide the selection of materials for the INIAF vegetable breeding program. The experiment was carried out in open field using 9 tomato lines in the farms of the National Center for Vegetable Seed Production, during the 2018-2019 agricultural season. A randomized complete block experimental design was used, with 3 replications and 10 plants per experimental unit. For data analysis, the yield variable was considered as the dependent variable and the variables number of flowers per inflorescence, number of clusters per plant, number of fruits per plant, fruit weight, equatorial and polar diameter as independent variables. Analysis of variance, phenotypic correlations and path coefficients were performed. The yield of line L015 was 80.79 t ha-1 higher than lines L014, L019 and Rio Grande. Fruit yield was significantly correlated with fruit weight per plant followed by polar diameter, equatorial diameter, number of fruits per plant and fruit weight. Path coefficient analysis was that the number of fruits per plant had the highest positive direct effect on fruit yield, fruit weight and polar diameter showing significant correlation and direct effect on fruit yield emerged as the components with coefficients 0.57, 0.33 and 0.46, respectively. These traits may be relevant within the selection criteria in the development of new varieties.